Optimal binary prefix-condition codes with ordinal probabilities - Greenberg, Irwin (Journal of the American Society for Information Science, 1990)
Probability estimates for letters in a finite alphabet are derived in order to apply the Huffman algorithm to determine an optimal binary prefix‐condition code. The estimates maximize the entropy subject to constraints specifying second‐level orderings of the letters' likelihoods. These are compared to estimates obtained from another probability estimation technique described in the decision theory literature using the English alphabet as an example. © 1990 John Wiley & Sons, Inc.